Multiple Myeloma Masquerading as Ovarian Carcinosarcoma Metastases: A Case Report and Review of the Approach to Multiple Myeloma Screening and Diagnosis. (24th September 2018) - Stuver, Robert; Petersen, Alec; Guerrero-Garcia, Thomas A.; Matulonis, Ursula; Richardson, Paul; Singh, Prabhsimranjot
Abstract : Multiple myeloma is the most common plasma cell dyscrasia and causes 2% of all cancer deaths in Western countries. Ovarian carcinosarcomas are very rare gynecological malignancies and account for only 1–2% of all ovarian tumors. In this case, we report a 67-year-old woman with known relapsed ovarian carcinosarcoma who presented with headache and neck pain. She was found to have new lytic lesions in the cranial and thoracic regions. While these lesions were assumed to be metastases, a diligent approach detected an M-spike on serum protein electrophoresis and a monoclonal gammopathy with immunoglobulin G lambda monoclonal immunoglobulin on immunofixation. A bone marrow biopsy confirmed the diagnosis of multiple myeloma. To our knowledge, this is the first ever reported case of concomitant multiple myeloma and ovarian carcinosarcoma. Our case highlights the utmost importance of a systematic approach to lytic lesions and emphasizes the need to consider secondary malignancies in the evaluation of possible metastases. We used the International Myeloma Working Group guidelines for screening and diagnosing multiple myeloma, and we provide a thorough review of this updated approach.